(untitled) (International Journal of Engineering and Computer Science, 2018)
Now a days, fire accidents are very common and sometimes it becomes very difficult for a fireman to save someone’s life. It is not possible to appoint a person to continuously observe for accidental fire where robot can do that. Therefore in such cases fire fighting robot comes in picture . Robot will detect fire remotely. These robots are mostly useful in industries where probability of accidental fire is more. The proposed vehicle is able to detect presence of fire and extinguishing it automatically by using gas sensor and temperature sensor. It contains gear motors and motor driver to control the movement of robot . Relay circuit is used to control the pump and when it will detect fire then it will communicate with microcontroller (Arduino UNO R3) through Bluetooth module. The proposed robot has a water jet spray which is capable of sprinkling water. The sprinkler can be move towards the required direction .At the time of moving towards the source of fire it may happen that it will come across some obstacles ,then it has obstacle avoiding capability. It will provide GUI for arduino operation using android. It detects obstacles using ultrasonic sensors upto range of 80 m. Communication between the mobile phone and robot will take place through Bluetooth ,which will have GUI to control the movement of robot . When mobile gets connected to Bluetooth firstly it will set module name, baud rate . It is feasible to implement Bluetooth communication between smartphones and microcontroller. Android controlled robot can be used easily in everyday life such as in homes, market ,companies etc. The development of apps for Android in Android SDK is easy and free of cost.